Efficacy of vaginal dilator use in preventing vaginal stenosis among cervical and endometrial cancer patients underwent radiotherapy - K., Varghese Mathew; C., Raphael Jomon; Febin, Antony; Malini, Mohan; Paul, Gopu (International Journal of Research in Medical Sciences, 2021)
Background: Vaginal dilators (VD) are effective in the prevention of vaginal stenosis in patients undergoing pelvic radiotherapy for gynaecological malignancies. This study was aimed to assess the efficacy of VD use in preventing post radiotherapy vaginal stenosis in cervical and endometrial cancer patients. Methods: A cohort study was designed among patients (20-70 years) with biopsy proven endometrial and cervical carcinoma who underwent pelvic radiotherapy were included. Patients with cervical carcinoma (FIGO stage-IA to IVA), endometrial carcinoma (FIGO stage IB grade III, FIGO stage II), histology of squamous cell carcinoma, adenocarcinoma and performance score-ECOG 1 were included in the study. Assessment included clinical history, general examination, pelvic examination at 3 monthly intervals till 1 year. Grading of vaginal stenosis was assessed using LENT SOMA grading system. Results: A total of 42 patients with 20 patients using vaginal dilators and 22 patients who refused to use VD were assigned. It was effective for 60% of VD users compared to 20% of nonusers (p=0.007) at 9 months follow up. While at 12 months follow up, it was effective for 58% of VD users compared to 16.6% of nonusers (p=0.066). Percent adherence was maximum in the 1st and 2ndquarter and declined to 61% by the 4th quarter. The total adherence was 97%. Conclusions: There was 55% vs 22.7% effectiveness to prevent the vaginal stenosis among VD users. All patients need proper counselling, motivation and support for regular usage of VD which will ultimately help in reducing the incidence of vaginal stenosis.